The Role Of Character-Based Curriculum In Forming Students Ethics And Morals - Cinta Tri Andalis Mendrofa (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
This study examines the impact of a character-based curriculum on students' ethical and moral development in educational settings. Using qualitative research methods, including lesson observations and teacher interviews, the research highlights the crucial role of character-based approaches in shaping students' ethical foundations. Results demonstrate that implementing programs fostering honesty, responsibility, and cooperation significantly contributes to positive personality development. These findings underscore the importance of character-based education, emphasizing not only academic performance but also the cultivation of ethical and moral character. The implications suggest the need for more comprehensive curricula to address social challenges and strengthen education's role in shaping students' character. Overall, the study provides valuable insights into the effectiveness of character-based education in fostering a holistic and positive learning environment.